An Improved, Highly Efficient Method for the Synthesis of Bisphenols - L. S. Patil; V. S. Suryawanshi; O. B. Pawar; N. D. Shinde (E-Journal of Chemistry)
An efficient synthesis of bisphenols is described by condensation of substituted phenols with corresponding cyclic ketones in presence of cetyltrimethylammonium chloride and 3-mercaptopropionic acid as a catalyst in extremely high purity and yields.